2003
DOI: 10.1002/jbm.a.10569
|View full text |Cite
|
Sign up to set email alerts
|

Engineered cellular response to scaffold architecture in a rabbit trephine defect

Abstract: Tight control of pore architecture in porous scaffolds for bone repair is critical for a fully elucidated tissue response. Solid freeform fabrication (SFF) enables construction of scaffolds with tightly controlled pore architecture. Four types of porous scaffolds were constructed using SFF and evaluated in an 8-mm rabbit trephine defect at 8 and 16 weeks (n = 6): a lactide/glycolide (50:50) copolymer scaffold with 20% w/w tri-calcium phosphate and random porous architecture (Group 1); another identical design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
59
0
5

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 22 publications
1
59
0
5
Order By: Relevance
“…Many studies have stated that an optimal scaffold for bone replacement should have a 3D geometry similar of that of the ingrowing trabecular bone, because it may be an effective approach for fast and efficient conduction of new bone across significant distances in these osteoconductive structures [11,12,13].The importance of the pore size and architecture for a scaffold relies on the fact that they are essential for controlling metabolic aspects such as the diffusion of oxygen, growth factors, and nutrients to the cells [14].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have stated that an optimal scaffold for bone replacement should have a 3D geometry similar of that of the ingrowing trabecular bone, because it may be an effective approach for fast and efficient conduction of new bone across significant distances in these osteoconductive structures [11,12,13].The importance of the pore size and architecture for a scaffold relies on the fact that they are essential for controlling metabolic aspects such as the diffusion of oxygen, growth factors, and nutrients to the cells [14].…”
Section: Discussionmentioning
confidence: 99%
“…88 The CAD data guides the UV beam onto the liquid surface, which is then lowered to enable the liquid photopolymer to cover the surface. 3DP 89 involves ink jet printing of a binder onto a ceramic, 23,87 polymer 25,31,74,88,117,119,124 or composite 86,93,97 powder surface, one layer at a time. The movement of the jet head, which dispenses the binder, is controlled by the CAD crosssectional data.…”
Section: Introductionmentioning
confidence: 99%
“…Simon et al showed that geometrical parameters (pore size and the spatial arrangement of pores) affect the pattern of bone ingrowth [38]. The ability to vary and control the level of the three different types of porosity (i.e.…”
Section: Scaffold Architecturementioning
confidence: 99%